Implementation possibilities for the concept of management accounting in the Republic of Macedonia - Koleva Blagica; Gjorgjieva-Trajkovska Olivera; Georgieva-Svrtinov Vesna (Ekonomski Pogledi, 2016)
The actual business conditions which are featured with great number of changes in the social and political system in the Republic of Macedonia have their impact in all the spheres of the social life, including the accounting-management profession. The fact that "the modern management is not compatible with obsolete accounting" is very often emphasized. As it is natural, the management accounting should be adjusted to the management needs. Starting with this statement, the research subject of this study will be the process of implementation and efficient functioning of the management accounting in the companies and organizations in the Republic of Macedonia, taking into consideration their impact on the success of the companies and their functioning. On the other hand, the scientific-empirical goal, on the basis of empirical research, is completely focused on the ways of implementing of the management accounting as one kind of contemporary approach of the managers in the organizations by the means of high management, undercovering completely the possibilities for efficient implementation and application of the management accounting concept in the Macedonian organizations.